HUBUNGAN MOTIVASI PERAWAT DENGAN KEPATUHAN PERAWAT DALAM PENERAPAN UNIVERSALPRECAUTION DI RSU RAJAWALI CITRA YOGYAKARTA - Yunita Andika Mau; Agus Sarwo Prayogi (Poltekkes Kemenkes Yogyakarta, 2018)
Background: The nurse is the hospital's most frequent source of contact with the patient, so as to prevent nurses and patients from the risk of contracting nosocomial infections the need for nurse motivation to improve adherence in the application of universal precautions. Objective: To know the relationship between nurse motivation and nurse compliance in the application of universal precaution in Rajawali Citra Yogyakarta general hospital. Method: Type of research using descriptive quantitative with cross sectional approach. Number of samples of 45 nurses with total sampling technique. Data analysis using Chi-Square analysis. Results: The results showed that there was a correlation between nurse motivation and nurse compliance in the application of universal precaution at RSU Rajawali Citra Yogyakarta p = 0,000 (?0,05) with correlation coefficient strength that is equal to 0,547 or medium relationship. Conclusion: There is a correlation between nurse motivation and nurse compliance in the application of universal precaution in RSU Rajawali Citra Yogyakarta with moderate relationship.